DETEKSI GEN PENYANDI Toxic Shock Syndrome Toxin-1 (tst) ISOLAT Staphylococcus aureus ASAL SUSU DAN SUSU KAMBING DENGAN METODE Polymerase Chain Reaction (PCR) - , Rony Marsyal Kunda ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Staphylococcus aureus is the main bacterium found in cowâs and goatâs milk. This kind of bacteria can infect humans and animals. In humans, S. aureus can cause several serious diseases, among others skin infections, endocarditis, pneumonia, osteomielitis, sepsis arthritis, encephalitis, meningitis, staphylococcal food poisoning (SPF) and toxic shock syndrome (TSS). One of the toxins produced by S. aureus is toxic shock syndrome toxin-1 (TSST-1) which causes multiple organ failure. The disorder is characterized by occurrence of fever, hypotension, digestive system disorder, endothelial cell, and vascular muscles. Staphylococcus aureus found in fresh milk can cause toxic shock syndrome (TSS) as a result of food poisoning. The objective of this study was to detect the existence of encoding gene of TSST-1 S. aureus isolate from cowâs and goatâs milk. The research is initiated by re-identification stage of S. aureus conventionally continued by identification based on molecular with the method of PCR. A number of 10 S. aureus isolates from cowâs and goatâs milk cultured in aerobics continued by Gram stain, catalase, coagulase, MSA, VJA and VP tests. The identification of S. aureus based on molecular conducted by 16S rRNA gene amplification continued with amplification of TSST-1 encoding gene as the target gene. The PCR product of TSST-1 encoding gene then sequenced to ensure whether the DNA fragment amplified is the TSST-1 encoding gene or not. The result of the research indicates that re-identification of S. aureus conventionally generating positive reaction of S. aureus species. Molecular identification of 16S rRNA gene amplification gives a good result by producing DNA fragment of 745 bp size and meets the target gene. The detection result of encoding gene TSST-1 gives negative result marked by DNA fragment which the size does not match the target gene. The alignment result of sequence isolate SA.1 indicates that the sequence is not tst gene but the gene which coded glutamate sintetase belongs to S. aureus, whereas sequence of isolate KI.8 is 50S rRNA gene belongs to S. saprophyticus.